Emissions of an agricultural engine using blends of diesel and hydrous ethanol - Farias, Marcelo Silveira de (2019)
The growing global demand of energy, the decrease of petroleum reserves and the current of environmental contamination problems, make it imperative to study renewable energy sources for use in internal combustion engines, in order to decrease the dependence on fossil fuels and reduce emissions of pollutant gases. This study aimed to evaluate the emissions of a diesel-cycle engine of an agricultural tractor that uses diesel S500 (B5) mixed with 3, 6, 9, 12 and 15% of hydrous ethanol. It determined emissions of CO2 (ppm), NOx (ppm), and opacity (k value) of gases. A standard procedure was applied considering eight operating modes (M1, M2, M3, M4, M5, M6, M7, and M8) by breaking with an electric dynamometer in a laboratory. The experimental design was completely randomized, with 60 replicates and a 6 x 8 factorial design. Greater opacity and gas emissions were observed when the engine operated with 3% ethanol, while lower emissions occurred with 12 and 15%. With these fuels, the reduction of opacity, CO2, and NOx, in relation to diesel oil, was 24.49 and 26.53%, 4.96 and 5.15%, and 6.59 and 9.70%, respectively. In conclusion, the addition of 12 and 15% ethanol in diesel oil significantly reduces engine emissions.